Synthesis of new Cu(II), Ni(II), and Cd(II)-(N-Glycyl-L-leucine) complexes as peptide metalloantibiotics for targeting pathogenic water with antioxidant effect investigation - Safaa S. Hassan; Eman F. Mohamed; Kirolos Maged; Salma Hassan; Alaa Omran Hamad; Shahinda Nasr; Salma Reda; Poula Nabil; Andrew George; Mohamed M. Shoukry; Samar A. Aly; Ahmed M. Mongy; et al. (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background In recent efforts to address the critical need for clean and portable water, we have focused on innovative methods to eliminate pathogenic microorganisms. To this aim, the N-Glycyl-L-leucine (Gly-Leu) peptide ligand was complexed with different transition metal ions [Cu(II), Ni(II), and Cd(II)] as new peptide metalloantibiotics. The compounds were characterized and examined using various analytical methods, including elemental analysis (CHN), Fourier transform infrared spectroscopy (FTIR), assessments of magnetic properties, molar conductivity, 1HNMR, thermogravimetric analysis (TGA), and mass spectroscopy. The ligand acted as a di-anionic molecule using the carboxylate and the deprotonated amide nitrogen atom. The coordination sites were completed with carbonyl oxygen atoms and a water molecule. The complexes showed polymeric structures using bridging carboxylate groups. Results The antibacterial properties of the synthesized metal chelate were evaluated using disk diffusion and minimum inhibitory concentration methods on bacterial organisms identified from water samples taken from the Nile River. At a 1 mg/mL dose, the Cu(II)-chelate showed the biggest inhibitory zone of 27 mm against Klebsiella pneumonia, with a MIC value of 62.5 μg/mL, greater than that of the common gentamicin medication. Molecular docking investigations supported these findings, showing that Cu(II)-chelate had the lowest binding energy of − 6.16 kcal/mol, indicating significant, beneficial interactions with the amino acids in the active region of bacterial proteins. Furthermore, the Cu(II) complex and the COVID-19 main protease showed encouraging results in the docking analysis, indicating that the complex may have antiviral properties and be able to inhibit viral propagation successfully. The metal chelates demonstrated noteworthy antioxidant activity, especially against 1,1-diphenyl-2-picrylhydrazyl (DPPH radicals). The IC50 values of the antioxidant assay for Ni(II) and Cu(II) chelates were extremely similar to ascorbic acid, a common antioxidant. Their notable antioxidant capacity was demonstrated by the IC50 values of (14.4, 15.5, and 18 µg/mL) for ascorbic acid, Ni(II), and Cu(II) chelates, respectively. Conclusions Our study successfully demonstrated the potential of a new Gly-Leu peptide ligand complexed with transition metal ions, particularly Cu(II), in eliminating pathogenic microorganisms from water. Cu(II)-chelate exhibited superior antibacterial properties, as confirmed by both experimental and molecular docking results. The chelates also displayed noteworthy antioxidant capacity, comparable to that of ascorbic acid. Additionally, the Cu(II)-chelate demonstrated promising antiviral potential, theoretically interacting effectively with the COVID-19 main protease, which suggests its ability to inhibit viral replication. These results underscore the potential of Cu(II)-chelate as a multi-functional compound with applications in water purification and therapeutic fields.